Structural Design, Synthesis, and Preliminary Biological Evaluation of Novel Dihomooxacalix[4]arene-Based Anti-tumor Agents - An, Lin; Wang, Chan; Han, Lili; Liu, Jiadong; Huang, Tonghui; Zheng, Youguang; Yan, Chaoguo; Sun, Jing (Frontiers in Chemistry, 2019)
Calixarene and its derivatives have extensively served as promising anti-tumor agents. Previously, we have synthesized a series of calix[n]arene polyhydroxyamine derivatives (n = 4, 6, 8) and found that 5,11,17,23-tetra-tert-butyl-25,27-bis [N-(2-hydroxyethyl)aminocarbonylmethoxyl] calix[4]arene (CLX-4) displayed significant effect toward SKOV3, A549, SW1990, HeLa, Raji, and MDA-MB-231 cancer cells. In the present work, we find a replacement of calix[4]arene bone and synthesized 19 novel structurally related dihomooxacalix[4]arene amide derivatives 4A−4S to optimize its efficacy. Their abilities to induce cytotoxicity in human lung carcinoma (A549) cells, breast cancer (MCF-7) cells, cervical cancer (HeLa) cells, hepatocellular carcinoma (HepG2) cells, as well as human umbilical vein endothelial (HUVEC) cells are evaluated in vitro. Encouraging results show that the majority of dihomooxacalix[4]arene amide derivatives are effective at inhibiting A549 cell proliferation with the corresponding IC50 ranging from 0.6 to 20.1 μM. In particular, compounds 4A, 4D, and 4L explore markedly increased potency (IC50 value is 2.0 ± 0.5 μM, 0.7 ± 0.1 μM, and 1.7 ± 0.4 μM) over the cytotoxicity profiles of control CLX-4, whose IC50 value is 2.8 ± 0.3 μM. More interestingly, 4A also demonstrates the perfect cytotoxic effect against MCF-7, HeLa, and HepG2 cells with IC50 values of 1.0 ± 0.1 μM, 0.8 ± 0.2 μM, and 2.7 ± 0.4 μM. In addition, the results proved that our synthesized 4A has much lower toxicity (41%) to normal cells at a concentration of 10 μM than that of 4D (90%). To reveal the mechanisms, the key indicators including the cell cycle and apoptosis are observed by the flow cytometry analysis in MCF-7 cells. The results demonstrate that both 4A and 4D can induce the MCF-7 cell cycle arrest in G0/G1 phase and cell apoptosis. Therefore, our finding proves that the dihomooxacalix[4]arene amide derivatives are convenient platforms for potential supramolecular anticancer agents.